Advances in protein dot blot: principles, technical specifics, applications, and future perspectives - Lu, Juan; Mai, Feng-yi; Li, Xin-yu; Yang, Wen-tao; Liang, Jing-rong; Li, Xing-long; Guo, Jie; Li, Chen-guang (Frontiers in Molecular Biosciences, 2026)
Protein dot blot is an efficient immunoblotting technique enabling qualitative/semi-quantitative protein analysis without electrophoresis, relying on antigen-antibody binding. Its workflow involves direct sample spotting on membranes, blocking, antibody incubation, and signal detection, completing within 3–5 h. Advantages include simplicity, high throughput, micro-sample compatibility, and cost-effectiveness, supporting basic life science research and clinical testing. However, it faces limitations like narrow dynamic range, inability to resolve protein variants, susceptibility to non-specific binding, and sensitivity to operational variables. This review systematically elaborates on its principles and procedures, analyzes key factors influencing sensitivity, and repeatability, and focuses on recent application progress in protein analysis, clinical biomarker detection, and food safety, along with technical innovations. It aims to provide comprehensive references for researchers and a theoretical basis for further optimization, with future advancements likely involving nanomaterial-based signal amplification, engineered antibodies, and integration with microfluidics or mass spectrometry to expand utility in biomedicine and public health.